Epidemiological Study of Intestinal Parasites in Referred Individuals to the Medical Centers’ Laboratories of Haji-Abad City, Hormozgan Province, Iran, 2015 - Mehran, Somayeh; Haghighi, Ali; Khazan, Hooshang; Azargashb, Eznoallah; Ghasemian Moghadam, Hamidreza (Novelty in Biomedicine, 2017)
Background:intestinal parasitic infection is one of the most prevalent health problems in developing countries. This study was conducted to determine the prevalence of intestinal parasitic infection and its correlation with socio-demographic parameters in Haji-abad, 2015. MaterialsandMethods:This cross-sectional descriptive study was conducted on 635 samples. After completing questionnaires, stool samples were assessed macroscopically, and microscopically using direct slide smear with saline and lugol, formalin-ether concentration, Ziehl-Neelsen staining to track Cryptosporidium species and Trichrome staining for the samples suspected to amoeba and other indeterminate cases. PCR using specific primers was conducted for Entamoebahistolytica/E. dispar suspected samples. The results were analyzed using SPSSver.16 software. Results:Of total 635 samples, 198 cases (31.2%) were infected by at least one intestinal parasite. The most common parasites in this area were: Blastocystis sp. (105, 16.5%), Endolimax nana (43, 6.8%), Entamoeba coli (32, 5.0%), Giardia lamblia (31, 4.9%), and Iodamoeba butschlii (11, 1.7%). Enterobius vermicularis (1, 0.2%) was the only detected helminthic infection. Regarding socio-demographic variables, age, residence, sampling month, and job showed a significant correlation with IPIs (p-value=0.031, 0.019, 0.014, 0.012; respectively). None of nine microscopically suspected E. histolytica/E. dispar cases were confirmed by molecular investigations (PCR method) and were considered as E. coli. Conclusion:In agreement with previous studies, helminthes infections show a dramatic decline compare to protozoa in this study. The relatively high incidence of intestinal protozoan infections in studies performed in Iran supports strategies for preventing the transmission and expansion of these parasites as a priority.